İNSAN DOĞASI ÜZERİNE - Halilrahman Açar (Felsefe Dünyası)
This essay attempts to bring a new approach into clarifying human nature from a different philosophical point of view. The author argues that past and present opinions on human nature cannot directly assert truth upon the subject because they are not adequate in nature. Therefore we must not remain within an offered framework. For this reason he provides us an alternative perspective by focusing on the phenomena of nafs. In this connection, the nafs is an emergent phenomenon. Then he proposes a set of claims concerning this phenomenon. Actually the term nafs which is taken together with its external and internal signification reveals itself as a whole and unity without going into a duality to man's nature. A t the same time, it refers to states or tendencies of human personality. That's why I draw the conclusion that the nafs alone as phenomena satisfactorily shows human nature. The text further explores consequences of this consideration.